An empirical study on the construct of "God" in the Twelve Step process. (1st November 2020) - Galanter, Marc; White, William L.; Ziegler, Penelope P.; Hunter, Brooke
ABSTRACT: Background : The term God, included in 5 of the 12 Steps of Narcotics Anonymous (NA) and Alcoholics Anonymous (AA), self-designated spiritual fellowships, has not been studied empirically relative to members' experiences. A greater understanding of this can be clinically useful and can shed light on the 12 Step process of recovery. Objectives : To determine how NA members understand the 12-step concept "God as we understood Him" and the relationship between their understanding of God and the intensity of their craving and depressive symptoms." Methods : 450 (59% male) NA members completed a survey related to their experiences relative to their relationship with "God." The relationship among these variables and comparisons to the general population was analyzed. Craving and depressive symptoms were assessed by self-report. Results : 98% of the NA participants believe in God explicitly or some other higher power (vs 89% of a probability sample of the US population), 67% believe that God determines what happens to them some or all of the time (vs 48%), 78% (vs 28%) report hearing God talking to them "in their mind"; and 37% report that God talks to them "out loud." Acceptance of 12 Step God-related variables inversely predicted a significant portion of the variance of scores on craving (7.5%) and depression (13.5%). Conclusions : Respondents' understanding of God in NA varied considerably and was predictive of their depressive symptoms and craving intensity. These findings can serve as a basis for research into mechanisms underlying NA/AA recovery experiences and can also aid clinicians in how to employ these programs.